Pengaruh Electronic Word Of Mouth, Brand Image Terhadap Minat Beli Produk Iphone Dengan Brand Trust Sebagai Variabel Intervening (Studi Kasus Pada Mahasiswa Manajemen Angkatan Tahun 2019 Universitas Muhammadiyah Metro) - Sri Agustinah; Fitriani; Durotun Nasikah (Universitas Muhammadiyah Metro, 2025)
Based on a report by the International Data Corporation (IDC), which published the company's latest report regarding the smartphone market in Indonesia for the fourth quarter of 2021, there are 5 smartphone brands with the highest market share in Indonesia in 2021 and iPhone is not included in the top 5. The aim is to find out whether the eWOM and Brand Image variables can have a direct effect on Brand Trust, to find out whether eWOM and Brand Image can have a direct effect on Buying Intention, to find out whether Brand Trust can have a direct effect on Buying Intention. This research uses a type of quantitative research method. The sampling technique uses the Accidental Sampling technique. Subjects who were interviewed as respondents were management students of the 2019 batch of Muhammadiyah Metro University who were found randomly. The data collection technique uses a questionnaire and literature study. and data analysis using validity test, reliability test, normality test, homogeneity test, linearity test and regression significance, and path analysis. The results of this study partially show that eWOM and Brand Image have a positive effect on Brand Trust. that eWOM and Brand Image have a positive effect on Purchase Intention, Brand Trust has a positive and significant effect on Purchase intention.